Microplastics elutriation system: Part B: Insight of the next generation. (August 2018) - Kedzierski, Mikaël; Le Tilly, Véronique; Bourseau, Patrick; César, Guy; Sire, Olivier; Bruzaud, Stéphane
Abstract: Elutriation is an efficient process for extracting microplastics. The development of a numerical model has shown the need for optimizing aspects of the design of the actual elutriation protocol as well as the dimensioning of the column to increase its efficiency. The study aims to propose new dimensioning data and protocol elements for designing an efficient column. Using a numerical model, the filling velocity was calculated as a function of the size and the density of the particles to prevent sand suspension. The sieving protocol was adapted to increase the density limit for the extraction of plastic particles from 1460 to >1800 kg·m −3 . The durations of the elutriation and the column height were calculated to improve the control of the particle suspension. These results contribute to the development of the next generation of elutriation system and will accelerate the study of plasticome in the context of sandy sediments. Highlights: The elutriation column is one of the best tools available for extracting plastics. Developing a system using elutriation technic is a scientific and technical issue. New dimensioning data for designing an efficient elutriation column are proposed. The elutriation duration and the column height can be optimized using this model.